Peran Moderasi Persepsi Dukungan Organisasi dalam Hubungan antara Pengaturan Kerja Fleksibel terhadap Kinerja - Nurul Nisa; Sanita Dhakirah; Fauziah Fauziah; Ayu Febriyanti Puspitasari (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2023)
The rise of flexible work systems such as work from home (WFH) offers opportunities for women to remain productive without leaving their households. However, WFH also presents unique challenges, particularly concerning the dual roles women often assume in balancing professional responsibilities and domestic duties. This study aims to examine the effect of flexible working arrangements on the performance of female employees, and to evaluate the moderating role of perceived organizational support (POS) in this relationship. Using a quantitative approach, data were collected through questionnaires distributed to 74 female workers in East Java who engage in WFH schemes. The data were analyzed using Partial Least Squares (PLS). The findings reveal that flexible working arrangements have a positive and significant effect on performance, and this relationship is further strengthened when employees perceive a high level of organizational support. These results underscore the importance of cultivating a supportive organizational climate, particularly for women navigating the challenges of dual roles while working remotely. Keywords: Flexible Working Arrangement, Perceived Organizational Support, Employee Performance, Work From Home, Women Workers